Composition for fire-extinguishing material, fire-extinguishing material, and device having automatic fire-extinguishing function

By adding compounds of acid anhydride groups and alkoxysilyl groups to the fire extinguishing agent composition, combined with vinyl ether monomer, the problem of easy delivery and slow reaction of the fire extinguishing agent is solved, and the long-term stability of the fire extinguishing material and the initial high-efficiency fire extinguishing effect are achieved.

JP2025018891APending Publication Date: 2025-02-06TOPPAN HOLDINGS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024006013
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-01-18
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

The existing self-extinguishing molding products contain salts such as potassium nitrate and sodium nitrate, which have easy dehydration problems, resulting in poor long-term stability and insufficient reaction under low fire conditions, and poor initial fire extinguishing effect.

Method used

A compound containing an anhydride group and an alkoxysilyl group is added to the fire extinguishing agent composition, and a structural unit containing a vinyl ether monomer is combined to form a stable fire extinguishing material composition, and the composition is optimized by controlling the proportion and thermogravimetric analysis of each component.

Benefits of technology

The long-term stability of fire extinguishing materials and the initial efficient fire extinguishing effect are achieved, the reactivity and stability of fire extinguishing materials are improved, and the rapid response in low fire situations is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018891000001_ABST
    Figure 2025018891000001_ABST
Patent Text Reader

Abstract

To provide a composition for a fire-extinguishing material that exhibits excellent stability in properties and enables early fire extinguishing with a sufficiently high probability.SOLUTION: The composition for a fire-extinguishing material comprises: a fire-extinguishing agent including at least one salt of deliquescent organic and inorganic salts; a component A, which is a binder resin; a component B, which is a compound having an acid anhydride group and an alkoxysilyl group; and a component C, which is a copolymer comprising a structural unit derived from a vinyl ether monomer and a structural unit derived from an unsaturated anhydrous carboxylic acid monomer. If the total mass of the components A, B and C corresponds to 100 pts.mass, then the content of the component A is greater than or equal to 1 pt.mass and less than 40 pts.mass, the content of the component B is greater than or equal to 10 pts.mass and less than 25 pts.mass, and the content of the component C is greater than or equal to 40 pts.mass and less than 90 pts.mass.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a fire-extinguishing composition, a fire-extinguishing material, and a device having automatic fire-extinguishing capabilities. [Background technology]

[0002] 2. Description of the Related Art A self-extinguishing molded article is known in which a fire extinguishing composition that generates an aerosol upon combustion is mixed with a binder and molded into a sheet (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2018 / 047762 [Patent Document 2] Patent No. 6443882 Summary of the Invention [Problem to be solved by the invention]

[0004] The fire extinguishing compositions described in Patent Documents 1 and 2 contain salts such as potassium nitrate and sodium nitrate. These salts are deliquescent, so there is room for improvement in terms of stably maintaining the properties of the self-extinguishing molded article for a long period of time. In addition, according to the inventors' studies, when assuming a small fire at the early stage of ignition, the reactivity of the self-extinguishing molded article is insufficient, and there is a certain probability that the fire may not be extinguished in the early stage, so there is room for improvement.

[0005] The present disclosure has been made in consideration of the above circumstances, and provides a fire extinguishing composition that has excellent property stability and can achieve initial fire extinguishing with a sufficiently high probability, a fire extinguishing material containing the fire extinguishing composition, and a device with an automatic fire extinguishing function that is equipped with the fire extinguishing material. [Means for solving the problem]

[0006] The present inventors have found that the property stability can be imparted to the fire extinguishing material by adding a compound having an acid anhydride group and an alkoxysilyl group to a fire extinguishing material composition containing at least one salt of an organic salt and an inorganic salt having deliquescent properties. The present inventors have conducted research to further improve the fire extinguishing performance of the fire extinguishing material while maintaining the effect of improving the property stability by the compound having an acid anhydride group and an alkoxysilyl group. As a result, it has been found that a fire extinguishing material composition that is excellent in property stability and can realize initial fire extinguishing with a sufficiently high probability can be obtained by further adding an appropriate amount of a copolymer containing a structural unit derived from a vinyl ether monomer and a structural unit derived from an unsaturated carboxylic anhydride monomer to a fire extinguishing material composition containing at least one salt of an organic salt and an inorganic salt having deliquescent properties, and a compound having an acid anhydride group and an alkoxysilyl group.

[0007] That is, one aspect of the present disclosure relates to a fire extinguishing composition including: a fire extinguishing agent containing at least one salt of an organic salt and an inorganic salt having deliquescent properties; component A which is a binder resin; component B which is a compound having an acid anhydride group and an alkoxysilyl group; and component C which is a copolymer including a structural unit derived from a vinyl ether monomer and a structural unit derived from an unsaturated carboxylic acid anhydride monomer. In the above fire extinguishing composition, when component A is heated from 30° C. to 500° C. at a heating rate of 5° C. / min in an atmospheric atmosphere, the weight loss rate of component A until the temperature reaches 400° C. is 50% or more, when component B is heated from 30° C. to 500° C. at a heating rate of 5° C. / min in an atmospheric atmosphere, the weight loss rate of component B until the temperature reaches 400° C. is less than 50%, and when component C is heated from 30° C. to 500° C. at a heating rate of 5° C. / min in an atmospheric atmosphere, the weight loss rate of component C until the temperature reaches 400° C. is 50% or more. In addition, when the total mass of component A, component B, and component C is 100 parts by mass, the content of component A is 1 part by mass or more and less than 40 parts by mass, the content of component B is 10 parts by mass or more and less than 25 parts by mass, and the content of component C is 40 parts by mass or more and less than 90 parts by mass. Such a fire extinguishing composition has excellent stability in properties and can achieve fire extinguishing at an early stage with a sufficiently high probability.

[0008] The content of the component A may be more than 10 parts by mass. A fire extinguishing material formed from a fire extinguishing material composition having a content of the component A within the above range is inhibited from cracking in the film and has excellent cut suitability.

[0009] The vinyl ether monomer may be methyl vinyl ether, and the unsaturated carboxylic anhydride monomer may be maleic anhydride. The acid anhydride group may be a carboxylic anhydride group, and the component B may be a silane coupling agent. The salt may be a potassium salt. The fire extinguishing composition may further include a liquid medium.

[0010] One aspect of the present disclosure relates to a fire extinguishing material including the fire extinguishing composition. Another aspect of the present disclosure relates to a device having an automatic fire extinguishing function including the fire extinguishing material. Effect of the Invention

[0011] According to the present disclosure, there are provided a fire extinguishing composition which has excellent property stability and can achieve initial fire extinguishing with a sufficiently high probability, a fire extinguishing material containing the fire extinguishing composition, and a device having an automatic fire extinguishing function which is equipped with the fire extinguishing material. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic diagram of one embodiment of a fire extinguishing material according to the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view that shows a schematic diagram of one embodiment of a fire extinguishing material package (a sheet-shaped fire extinguishing material contained in a packaging bag) according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, embodiments of the present disclosure will be described in detail. However, the present disclosure is not limited to the following embodiments.

[0014] <Composition for fire extinguishing material> The fire extinguishing material composition according to this embodiment includes a fire extinguishing agent containing at least one of an organic salt and an inorganic salt having deliquescent properties, component A which is a binder resin, component B which is a compound having an acid anhydride group and an alkoxysilyl group, and component C which is a copolymer containing a structural unit derived from a vinyl ether monomer and a structural unit derived from an unsaturated carboxylic acid anhydride monomer.

[0015] When the total mass of component A, component B, and component C contained in the fire extinguishing composition is 100 parts by mass, the content of component A is 1 part by mass or more and less than 40 parts by mass. The lower limit of the content may be 10 parts by mass, 20 parts by mass, or 25 parts by mass. When the content is equal to or more than the lower limit, component A can play a role as a binder that fixes the fire extinguishing agent as a coating film, and not only does the coating suitability of the fire extinguishing composition increase and film formation become easier, but cracking of the film can also be suppressed. In particular, from the viewpoint of cut suitability, the content is preferably more than 10 parts by mass. The upper limit of the content may be 33 parts by mass or 30 parts by mass. When the content is equal to or less than the upper limit, it becomes possible to add sufficient amounts of component B and component C to the fire extinguishing composition, which makes it easier to achieve both property stability and fire extinguishing performance at the beginning of ignition.

[0016] When the total mass of components A, B, and C contained in the fire extinguishing composition is 100 parts by mass, the content of component B is 10 parts by mass or more and less than 25 parts by mass. The lower limit of the content may be 13 parts by mass or 15 parts by mass. When the content is equal to or more than the lower limit, it is easy to suppress deliquescence of salt. The upper limit of the content may be 23 parts by mass, 20 parts by mass, or 18 parts by mass. When the content is equal to or less than the upper limit, it is easy to exhibit sufficient fire extinguishing performance.

[0017] When the total mass of component A, component B, and component C contained in the fire extinguishing composition is 100 parts by mass, the content of component C is 40 parts by mass or more and less than 90 parts by mass. The lower limit of the content may be 50 parts by mass, 55 parts by mass, or 59 parts by mass. When the content is equal to or more than the lower limit, sufficient fire extinguishing performance is easily exhibited. The upper limit of the content may be 89 parts by mass, 81 parts by mass, or 75 parts by mass. When the content is equal to or less than the upper limit, not only is it easy to suppress deliquescence of the salt, but it is also possible to add a sufficient amount of component A to the fire extinguishing composition, which increases the coating suitability of the fire extinguishing composition, makes it easy to form a film, and suppresses cracking of the film.

[0018] (Fire extinguishing agent) The extinguishing agent includes at least one of an organic salt and an inorganic salt having deliquescent properties, and an oxidizing agent. Examples of the organic salt include potassium salts, sodium salts, and ammonium salts. Of these, it is preferable to use potassium salts as the organic salt. Examples of the organic potassium salts include potassium carboxylates such as potassium acetate, potassium citrate (monopotassium citrate, dipotassium citrate, and tripotassium citrate), potassium tartrate, potassium lactate, potassium oxalate, and potassium maleate. Among these, it is preferable to use potassium acetate or potassium citrate from the viewpoint of usefulness in terms of the negative catalytic effect of combustion.

[0019] Examples of inorganic salts include potassium salts and sodium salts. Of these, it is preferable to use potassium salts as the inorganic salt. Examples of inorganic potassium salts include potassium tetraborate, potassium carbonate, potassium hydrogen carbonate, potassium dihydrogen phosphate, and dipotassium hydrogen phosphate.

[0020] The organic salts and inorganic salts may be used alone or in combination of two or more kinds.

[0021] The organic salt and inorganic salt may be granular. The average particle diameter D50 of the organic salt and inorganic salt may be 1 μm or more and 100 μm or less, or 3 μm or more and 40 μm or less. When the average particle diameter D50 is equal to or more than the lower limit, the salt is easily dispersed in the system. When the average particle diameter D50 is equal to or less than the upper limit, the stability of the salt when used as a coating liquid is improved, and the smoothness of the coating surface tends to be improved. The average particle diameter D50 can be calculated by wet measurement using a laser diffraction particle size distribution measuring device.

[0022] Examples of the oxidizing agent include potassium chlorate, sodium chlorate, strontium chlorate, ammonium chlorate, magnesium chlorate, potassium nitrate, sodium nitrate, strontium nitrate, ammonium perchlorate, potassium perchlorate, basic copper nitrate, copper (I) oxide, copper (II) oxide, iron (II) oxide, iron (III) oxide, molybdenum trioxide, etc. Among these, it is preferable to use potassium chlorate.

[0023] The content of the extinguishing agent in the composition for extinguishing material may be 70% by mass or more and 97% by mass or less, or 85% by mass or more and 92% by mass or less, based on the total amount (solid content) of the composition for extinguishing material. By having the content of the extinguishing agent be equal to or less than the upper limit, it is easy to suppress deliquescence of the salt, and the coating suitability of the composition for extinguishing material is improved, making it easy to form a film. In addition, by having the content of the extinguishing agent be equal to or more than the lower limit, it is easy to exhibit sufficient fire extinguishing performance.

[0024] (Binder resin (component A)) It is preferable that component A is easily reduced in weight by heat. That is, in thermogravimetry under an air atmosphere, when component A is heated from 30°C to 500°C at a heating rate of 5°C / min, the weight reduction rate of component A until the temperature reaches 400°C is 50% or more. The lower limit of the weight reduction rate may be 60%. When the weight reduction rate is within the above range, the resulting fire extinguishing performance at the initial stage of ignition is excellent. Note that, when there are multiple components A, the weight reduction rate of component A means the weight reduction rate of the mixture. The upper limit of the weight reduction rate may be, for example, 88%, or may be 80% or 70%.

[0025] Thermoplastic resins and thermosetting resins can be used as component A. Examples of thermoplastic resins include polyolefin resins such as polyvinyl alcohol resins, polyvinyl acetal resins, polypropylene resins, polyethylene resins, poly(1-)butene resins, and polypentene resins, polystyrene resins, acrylonitrile-butadiene-styrene resins, methyl methacrylate-butadiene-styrene resins, ethylene-vinyl acetate resins, ethylene-propylene resins, polycarbonate resins, polyphenylene ether resins, acrylic resins, polyamide resins, and polyvinyl chloride resins. Examples of thermosetting resins include rubbers such as natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), 1,2-polybutadiene rubber (1,2-BR), styrene-butadiene rubber (SBR), chloroprene rubber (CR), nitrile rubber (NBR), butyl rubber (IIR), ethylene-propylene rubber (EPR, EPDM), chlorosulfonated polyethylene (CSM), acrylic rubber (ACM, ANM), epichlorohydrin rubber (CO, ECO), multi-vulcanized rubber (T), silicone rubber (Q), fluororubber (FKM, FZ), and urethane rubber (U), polyurethane resins, polyisocyanate resins, polyisocyanurate resins, phenolic resins, and epoxy resins. Of the above resins, one may be used alone, or multiple types may be used in combination. Of these, it is preferable to use a polyurethane resin or a polyvinyl alcohol resin from the viewpoint of coating suitability. In addition, component A may contain a curing agent component.

[0026] The weight average molecular weight of component A may be 5000 or more, 20000 or more, or 150000 or less, or 100000 or less. When the weight average molecular weight is the lower limit or more, the hydrophobicity of the resin is easily ensured. When the weight average molecular weight is the upper limit or less, the appropriate resin flexibility is easily ensured, and the bending resistance and coating suitability are easily improved. The weight average molecular weight can be calculated by the GPC method.

[0027] The glass transition temperature of component A is not particularly limited, but may be -40°C or higher, 55°C or higher, or 80°C or higher, and may be 110°C or lower, or 100°C or lower. When the glass transition temperature is above the lower limit, the crystallinity is increased, and therefore the hydrophobicity of the resin is easily ensured. When the glass transition temperature is below the upper limit, the coating suitability is easily improved. The glass transition temperature can be measured by thermal analysis using a differential scanning calorimeter.

[0028] The viscosity of the resin solution in which component A is dissolved in a liquid medium at 20°C may be 500 mPa·s or more, or 1000 mPa·s or more, or 10000 mPa·s or less, or 6000 mPa·s or less. The viscosity can be measured by a B-type rotational viscometer.

[0029] (Compound having an acid anhydride group and an alkoxysilyl group (Component B)) The fire extinguishing material composition can stably maintain the properties of the molded article for a long period of time by including component B. Although the reason for this is unclear, it is speculated that this is due to the fact that the acid anhydride group can react with water, trapping water that has penetrated through the barrier film used to package the fire extinguishing material, thereby preventing deliquescence of the salt contained in the molded article, and / or that after the alkoxysilane is hydrolyzed, a self-reaction occurs to form siloxane, thereby improving water resistance and film density, and suppressing contact between the deliquescent salt and water.

[0030] Component B is less susceptible to weight loss due to heat compared to component A and component C. That is, in thermogravimetry under an air atmosphere, when component B is heated from 30°C to 500°C at a heating rate of 5°C / min, the weight loss rate of component B until the temperature reaches 400°C is less than 50%. The upper limit of the weight loss rate may be 40%, or may be 30%, 20%, or 15%. When the weight loss rate is within the above range, the property stability of the obtained fire extinguishing material composition is excellent. Note that, when there are multiple components B, the weight loss rate of component B means the weight loss rate of the mixture. The lower limit of the weight loss rate may be, for example, 0%, 3%, or 7%.

[0031] Component B is not particularly limited as long as it is a compound having one or more acid anhydride groups in the molecule formed by dehydration condensation of two oxoacid molecules, and further having one or more alkoxysilyl groups in the molecule. Examples of oxoacids that form an acid anhydride group include carboxylic acid, sulfuric acid, nitric acid, phosphoric acid, etc. Among these, it is preferable that the oxoacid that forms the acid anhydride group is a carboxylic acid. Examples of compounds having a carboxylic acid anhydride group include simple carboxylic acid anhydrides such as phthalic anhydride, succinic anhydride, and maleic anhydride, and copolymers in which a carboxylic acid anhydride having an unsaturated bond such as maleic anhydride is used as a monomer.

[0032] For example, a silane coupling agent may be used as Component B. The silane coupling agent used as Component B may have the same function as the binder resin in the fire extinguishing material composition.

[0033] (Copolymer containing structural units derived from vinyl ether monomers and structural units derived from unsaturated carboxylic anhydride monomers (Component C)) By including component C, the composition for fire extinguishing material can stably maintain the properties of the molded article for a long period of time and can realize initial fire extinguishing with a sufficiently high probability. Although the reason for this is unclear, it is presumed that the structural unit derived from the vinyl ether monomer contributes to improving the fire extinguishing performance, and the structural unit derived from the unsaturated carboxylic anhydride monomer contributes to improving the stability of properties. Component C may have the same function as a binder resin in the composition for fire extinguishing material, but is distinguished from component A in that it is a copolymer containing a structural unit derived from a vinyl ether monomer and a structural unit derived from an unsaturated carboxylic anhydride monomer.

[0034] It is preferable that component C is easily reduced in weight by heat. That is, in thermogravimetry under an air atmosphere, when component C is heated from 30°C to 500°C at a heating rate of 5°C / min, the weight reduction rate of component C is 50% or more until the temperature reaches 400°C. The lower limit of the weight reduction rate may be 55%. When the weight reduction rate is within the above range, the resulting fire extinguishing composition has excellent fire extinguishing performance at the beginning of ignition. In addition, when there are multiple components C, the weight reduction rate of component C means the weight reduction rate of the mixture. The upper limit of the weight reduction rate may be, for example, 80%, 70% or 60%.

[0035] Component C is obtained, for example, by copolymerizing a vinyl ether monomer and an unsaturated carboxylic anhydride monomer. Examples of the vinyl ether monomer include alkyl vinyl ethers such as methyl vinyl ether and ethyl vinyl ether. Of these, the vinyl ether monomer is preferably methyl vinyl ether. Examples of the unsaturated carboxylic anhydride monomer include maleic anhydride and citraconic anhydride. Of these, the unsaturated carboxylic anhydride monomer is preferably maleic anhydride.

[0036] The total content of components A, B, and C contained in the fire extinguishing composition may be 3 mass% or more and 30 mass% or less, 5 mass% or more and 20 mass% or less, or 8 mass% or more and 15 mass% or less, based on the total amount (solid content) of the fire extinguishing composition.

[0037] (Liquid medium) The fire extinguishing material composition may further include a liquid medium. The liquid medium may be an organic solvent. The organic solvent may be a water-soluble solvent, for example, alcohols such as methanol, ethanol, isopropyl alcohol, n-propyl alcohol, etc.; ketones such as acetone, methyl ethyl ketone, etc.; glycols such as ethylene glycol, diethylene glycol, etc.; glycol ethers such as N-methylpyrrolidone, tetrahydrofuran, butyl cellosolve, etc. From the viewpoint of being used together with a salt, the liquid medium may be an alcohol-based solvent.

[0038] The amount of the liquid medium may be appropriately adjusted depending on the method of use of the fire extinguishing material composition, but may be 30% by mass or more and 70% by mass or less based on the total amount of the fire extinguishing material composition (including the liquid medium). The fire extinguishing material composition containing the liquid medium can be called a fire extinguishing material coating liquid.

[0039] (Other Ingredients) The composition for fire extinguishing material may contain other components in addition to those mentioned above. Examples of other components include surfactants, antiblocking agents, colorants, antioxidants, flame retardants, inorganic fillers, fluidity imparting agents, moisture-proofing agents, dispersants, UV absorbers, softening agents, catalysts, etc. These other components can be appropriately selected depending on the type of the fire extinguishing agent, component A, component B, component C, or liquid medium, etc. The content of other components contained in the composition for fire extinguishing material can be 10 mass% or less based on the total amount of the composition for fire extinguishing material.

[0040] The fire extinguishing composition can be produced by mixing a fire extinguishing agent containing at least one of an organic salt and an inorganic salt having deliquescent properties, component A, component B, component C, and other components used as necessary.

[0041] <Fire extinguishing material> The extinguishing material can be formed from the extinguishing material composition. FIG. 1 is a cross-sectional view showing a schematic diagram of one embodiment of the extinguishing material. The extinguishing material 1 includes a substrate 2 and an extinguishing material layer 3 provided on one surface of the substrate 2. The extinguishing material 1 can be manufactured through a process of applying a coating liquid for the extinguishing material on one surface of the substrate 2 and a process of drying the applied layer to form the extinguishing material layer 3. The material of the substrate 2 is, for example, metal, resin, wood, ceramics, or glass, and may be non-porous or porous.

[0042] The application can be carried out by a wet coating method, such as gravure coating, comma coating, spray coating, dip coating, curtain coating, spin coating, sponge roll coating, die coating, or brush coating.

[0043] The viscosity of the fire-extinguishing material coating liquid is preferably 1 to 2000 mPa·s in the case of the gravure coating method, 500 to 100000 mPa·s in the case of the comma coating method, and 0.1 to 4000 mPa·s in the case of the spray coating method. The amount of the liquid medium may be appropriately adjusted so that the coating liquid viscosity falls within the desired range. The viscosity can be measured using a coaxial double cylinder rotational viscometer.

[0044] When the substrate 2 is porous, the fire-extinguishing material coating liquid can penetrate into the substrate 2. In this case, a part of the fire-extinguishing material layer 3 may penetrate into the substrate 2, and the remainder may be laminated on the surface of the substrate 2.

[0045] The fire extinguishing material can be obtained by forming the fire extinguishing material composition into a predetermined shape. The shape of the fire extinguishing material may be selected depending on the application, and the fire extinguishing material may be a granular fire extinguishing material, a plate-shaped fire extinguishing material, a columnar fire extinguishing material, or the like.

[0046] <Devices with automatic fire extinguishing function> A device with an automatic fire extinguishing function is equipped with a fire extinguishing material. Examples of devices with an automatic fire extinguishing function include electrical wiring and cables, and electrical system equipment equipped with transformers and electrical circuits. Specific examples include distribution boards, switchboards, storage batteries (lithium ion batteries, etc.), batteries (mobile batteries, tool batteries, EV batteries for automobiles, etc.), and power storage systems equipped with the above. Further examples include places where there is a risk of unintended fire, such as collection boxes for storage batteries, trash cans, and outlet covers.

[0047] The present disclosure relates to the following: [1] A fire extinguishing agent containing at least one salt selected from the group consisting of an organic salt and an inorganic salt having deliquescent properties; Component A is a binder resin; Component B is a compound having an acid anhydride group and an alkoxysilyl group; Component C is a copolymer comprising structural units derived from vinyl ether monomers and structural units derived from unsaturated carboxylic anhydride monomers; Including, In a thermogravimetric measurement under an atmospheric condition, when the component A is heated from 30°C to 500°C at a heating rate of 5°C / min, the weight loss rate of the component A until the temperature reaches 400°C is 50% or more; In a thermogravimetric measurement under an atmospheric condition, when component B is heated from 30° C. to 500° C. at a heating rate of 5° C. / min, the weight loss rate of component B until the temperature reaches 400° C. is less than 50%, In a thermogravimetric measurement under an atmospheric condition, when the component C is heated from 30°C to 500°C at a heating rate of 5°C / min, the weight loss rate of the component C until the temperature reaches 400°C is 50% or more; When the total mass of the component A, the component B, and the component C is 100 parts by mass, The content of the component A is 1 part by mass or more and less than 40 parts by mass, The content of the component B is 10 parts by mass or more and less than 25 parts by mass, A fire extinguishing composition, wherein the content of component C is 40 parts by mass or more and less than 90 parts by mass. [2] The fire extinguishing composition according to [1], wherein the content of component A is more than 10 parts by mass. [3] The fire extinguishing composition according to [1] or [2], wherein the vinyl ether monomer is methyl vinyl ether. [4] The fire extinguishing composition according to any one of [1] to [3], wherein the unsaturated carboxylic anhydride monomer is maleic anhydride. [5] The fire extinguishing composition according to any one of [1] to [4], wherein the acid anhydride group is a carboxylic acid anhydride group. [6] The fire extinguishing composition according to any one of [1] to [5], wherein the component B is a silane coupling agent. [7] The fire extinguishing composition according to any one of [1] to [6], wherein the salt is a potassium salt. [8] The fire extinguishing composition according to any one of [1] to [7], further comprising a liquid medium. [9] A fire extinguishing material formed from the fire extinguishing material composition according to any one of [1] to [8].

[10] [9] An apparatus having an automatic fire extinguishing function, comprising the fire extinguishing material described in the above. EXAMPLES

[0048] The present disclosure will be described more specifically below based on examples, but the present disclosure is not limited to the following examples.

[0049] The following materials were used in the examples and comparative examples. (Fire extinguishing agent) Organic potassium salts: tripotassium citrate Oxidizing agent: Potassium chlorate (KClO3) Tripotassium citrate is a deliquescent salt. (Component A: Binder resin) Ether-based polyurethane resin (weight reduction rate: 88.0%) (Resin solution of component A) An ether-based polyurethane resin solution obtained by dissolving 100 parts by mass of ether-based polyurethane resin in 210 parts by mass of isopropyl alcohol. (Component B: Compound having an acid anhydride group and an alkoxysilyl group) Silane coupling agent having an acid anhydride group and an alkoxysilyl group (manufactured by Shin-Etsu Chemical Co., Ltd., product name: X-12-1287A) (weight loss rate: 11.8%) (Component C: Copolymer containing structural units derived from vinyl ether monomers and structural units derived from unsaturated carboxylic anhydride monomers) Polymethyl vinyl ether (PMVE) / maleic anhydride copolymer (manufactured by Ashland Japan Co., Ltd., product name: Gantrez AN-119) (weight loss rate: 60.0%) (Liquid medium) ethanol (Resin substrate) Polyethylene terephthalate (PET) substrate (Toyobo Co., Ltd., product name: E7002, thickness 50 μm)

[0050] <Weight change rate measurement> The weight change rates of components A, B, and C were measured when they were heated from 30° C. to 500° C. at a rate of 5° C. / min in an air atmosphere and then to 400° C. using a differential thermal thermogravimetry device "STA7200RV" manufactured by Hitachi High-Tech Science Corp. The sampling period was 1 second.

[0051] <Formation of Fire Extinguishing Composition> Example 1 A mixture of tripotassium citrate and KClO3 was pulverized in an agate mortar so that the average particle size D50 was 12 μm or less. 87.4 parts by mass of the pulverized mixture, a mixture in which the total mass of the resin solution of component A, the solid content of component B, and the solid content of component C was 12.6 parts by mass, and the contents of each component were 1 part by mass, 10 parts by mass, and 89 parts by mass when the total mass of component A, component B, and component C was 100 parts by mass, respectively, were mixed with 87 parts by mass of ethanol and stirred to obtain a fire extinguishing composition.

[0052] (Examples 2 to 9, Comparative Examples 1 to 13) A fire extinguishing composition was obtained in the same manner as in Example 1, except that the above contents of Component A, Component B, and Component C were changed to the contents shown in Table 1. The contents shown in Table 1 refer to the contents of each component when the total mass of Component A, Component B, and Component C is taken as 100 parts by mass.

[0053] <Fire extinguishing material formation> The fire extinguishing composition obtained in each example was applied to a PET substrate using an applicator, and then dried in an oven at 75°C for 7 minutes to obtain a laminate in which a sheet-like fire extinguishing material having a thickness of 150 μm was formed on the PET substrate.

[0054] <Various tests> A barrier film (water vapor permeability is 0.2 to 0.6 g / (m)) including a sealant layer 5 (L-LDPE (linear low-density polyethylene) resin, thickness 30 μm) and a base layer 6 (PET resin with a silica vapor deposition film, thickness 12 μm) 2 A sheet-shaped fire extinguishing material (50 mm x 50 mm) was covered with two of these barrier films, and the four sides of the barrier film were heat-sealed to enclose the sheet-shaped fire extinguishing material. The heat sealing conditions were 140°C and 2 seconds. The heat seal width of each side was 10 mm. As a result, a fire extinguishing material package 20 (sheet-shaped fire extinguishing material 10 contained in a packaging bag 4) with outer dimensions of 70 mm x 70 mm as shown in Figure 2 was obtained. This was used as an evaluation sample. The evaluation samples obtained from each example were tested as follows. The results are shown in Table 1.

[0055] <Property stability test> The total light transmittance of the evaluation sample was measured using a haze meter (BYK-Gardner Haze-Guard Plus manufactured by BYK) according to a method conforming to JIS K 7361-1. The measurement was performed after 168 hours had elapsed since it was placed in a thermo-hygrostat (under conditions of 85°C / 85%RH). This operation was performed three times at different measurement points, and the average value was recorded. As the deliquescence of the salt progresses, the transparency of the fire extinguishing material increases and the value of the total light transmittance increases, so the degree of deliquescence was evaluated by measuring the total light transmittance. When the salt is less likely to deliquescence (for example, the value of the total light transmittance is 50% or less), the property stability of the fire extinguishing material is high. The total light transmittance of the barrier film was 85%.

[0056] <Fire extinguishing performance test> An iron container measuring 20 cm in length, 30 cm in width, and 40 cm in height was prepared. Five circular vents with a diameter of 8.5 mm were provided on each side of the container at heights of 5.0 cm, 12.5 cm, 20.0 cm, 27.5 cm, and 35.0 cm from the top surface to prevent the ignited solid fuel from suffocating. A fire extinguishing material package (evaluation sample) was attached to the center of the top surface of the container with double-sided tape. 1.5 g of solid fuel (Captain Stag Co., Ltd. solid fuel fire block ignition agent) measuring 15 mm in length, 15 mm in width, and 10 mm in height was placed in the center of the bottom surface of the container. The distance between the solid fuel and the evaluation sample was adjusted to 20 cm, and a test was conducted to see whether the evaluation sample could be extinguished within 180 seconds after the solid fuel was ignited. The above test was repeated multiple times, and the probability of successful extinguishing was recorded.

[0057] <Cutting suitability evaluation test> The laminate on which the fire extinguishing material was formed was cut with a cutter from the surface side of the fire extinguishing material, and the presence or absence of chipping of the fire extinguishing material coating film and peeling from the substrate was visually confirmed. The evaluation was performed based on the following criteria. A: No chipping of the coating film or peeling from the substrate is observed. B: The coating film is partially chipped and peeled off from the substrate. C: Chipping of the coating and peeling from the substrate occurs over the entire area.

[0058] [Table 1] In the table, the numbers in parentheses for the probability of successful extinguishing the fire mean (number of successful extinguishing attempts / number of tests). [Explanation of symbols]

[0059] 1...fire extinguishing material, 2...substrate, 3...fire extinguishing material layer, 4...packaging bag, 5...sealant layer, 6...substrate layer, 10...fire extinguishing material, 20...fire extinguishing material package.

Claims

1. a fire extinguishing agent containing at least one salt selected from the group consisting of an organic salt and an inorganic salt having deliquescent properties; Component A is a binder resin; Component B is a compound having an acid anhydride group and an alkoxysilyl group; Component C is a copolymer including a structural unit derived from a vinyl ether monomer and a structural unit derived from an unsaturated carboxylic anhydride monomer and is different from component A; A fire extinguishing composition comprising: When the total mass of the component A, the component B, and the component C is 100 parts by mass, The content of the component A is 13 parts by mass or more and less than 40 parts by mass, The content of the component B is 10 parts by mass or more and less than 25 parts by mass, A fire extinguishing composition, wherein the content of component C is 40 parts by mass or more and 75 parts by mass or less.

2. The fire extinguishing composition according to claim 1, wherein the content of the component A is more than 10 parts by mass.

3. 2. The fire extinguishing composition of claim 1, wherein the vinyl ether monomer is methyl vinyl ether.

4. 2. The fire extinguishing composition according to claim 1, wherein the unsaturated carboxylic anhydride monomer is maleic anhydride.

5. 2. The fire extinguishing composition according to claim 1, wherein the acid anhydride group is a carboxylic acid anhydride group.

6. 2. The fire extinguishing composition according to claim 1, wherein said component B is a silane coupling agent.

7. 2. The fire extinguishing composition of claim 1, wherein the salt is a potassium salt.

8. 10. The fire extinguishing composition of claim 1, further comprising a liquid medium.

9. A fire extinguishing material comprising the fire extinguishing material composition according to any one of claims 1 to 8.

10. A device having an automatic fire extinguishing function, comprising the fire extinguishing material according to claim 9.

Citation Information

Patent Citations

  • Magnetic tape cassette

    JP1989043882A

  • Self-extinguishing molded article

    WO2018047762A1